ISLAMIC FINANCIAL LITERACY, ISLAMIC FINANCIAL INCLUSIVENESS, AND RELIGIOSITY INCREASE THE INTENTION TO SAVE IN SHARIA BANKS - Listiani, Nur; Mardika, Dhoni Rizky Widya; Tahwin, Muhammad (STIE Pelita Nusantara Semarang, 2025)
The inclination to save in Islamic banks indicates the public's acceptance and utilization of Islamic banking savings products. Comprehending the determinants affecting this purpose is crucial for Islamic banks to formulate tactics that promote increased engagement. This study examines the impact of Islamic Financial Literacy (IFL), Islamic Financial Inclusiveness (IFI), and religiosity on students' intentions to save in Islamic banks. The study sample consists of persons who have completed courses in Islamic banking, and the data were analyzed using multiple linear regression techniques. The findings demonstrate that IFL, IFI, and religiosity each have a substantial and affirmative impact on the intention to save in Islamic banks. The findings indicate that Islamic banks ought to intensify initiatives to elevate financial literacy, broaden financial inclusivity, and promote religiosity among prospective clients, thus augmenting the use of Islamic banking products and allowing a greater number of individuals to derive benefits from them.